Neutrophil GM-CSF receptor dynamics in acute lung injury. Issue 6 (3rd April 2019) - De Alessandris, Silvia; Ferguson, G John; Dodd, Alison J; Juss, Jatinder K; Devaprasad, Abhinandan; Piper, Siân; Wyatt, Owen; Killick, Helen; Corkill, Dominic J; Cohen, E Suzanne; Pandit, Aridaman; Radstake, Timothy R D J; et al.
Abstract: GM-CSF is important in regulating acute, persistent neutrophilic inflammation in certain settings, including lung injury. Ligand binding induces rapid internalization of the GM-CSF receptor (GM-CSFRα) complex, a process essential for signaling. Whereas GM-CSF controls many aspects of neutrophil biology, regulation of GM-CSFRα expression is poorly understood, particularly the role of GM-CSFRα in ligand clearance and whether signaling is sustained despite major down-regulation of GM-CSFRα surface expression. We established a quantitative assay of GM-CSFRα surface expression and used this, together with selective anti-GM-CSFR antibodies, to define GM-CSFRα kinetics in human neutrophils, and in murine blood and alveolar neutrophils in a lung injury model. Despite rapid sustained ligand-induced GM-CSFRα loss from the neutrophil surface, which persisted even following ligand removal, pro-survival effects of GM-CSF required ongoing ligand-receptor interaction. Neutrophils recruited to the lungs following LPS challenge showed initially high mGM-CSFRα expression, which along with mGM-CSFRβ declined over 24 hr; this was associated with a transient increase in bronchoalveolar lavage fluid (BALF) mGM-CSF concentration. Treating mice in an LPS challenge model with CAM-3003, an anti-mGM-CSFRα mAb, inhibited inflammatory cell influx into the lung and maintained the level of BALF mGM-CSF. Consistent with neutrophil consumption of GM-CSF, human neutrophils depleted exogenous GM-CSF, independent of protease activity. These data show that loss of membrane GM-CSFRα following GM-CSF exposure does not preclude sustained GM-CSF/GM-CSFRα signaling and that this receptor plays a key role in ligand clearance. Hence neutrophilic activation via GM-CSFR may play an important role in neutrophilic lung inflammation even in the absence of high GM-CSF levels or GM-CSFRα expression. Graphical Abstract: GM-CSF released during ALI stimulates neutrophil recruitment, induces down-regulation of GM-CSFR, and GM-CSF consumption by neutrophils, yet sustained anti-apoptotic signals require continued GM-CSF stimulation.